Effects of shear stress pattern and magnitude on mesenchymal transformation and invasion of aortic valve endothelial cells. Issue 11 (5th August 2014) - Mahler, Gretchen J.; Frendl, Christopher M.; Cao, Qingfeng; Butcher, Jonathan T.
ABSTRACT Understanding the role of mechanical forces on cell behavior is critical for tissue engineering, regenerative medicine, and disease initiation studies. Current hemodynamic bioreactors are largely limited to 2D substrates or the application of general flow conditions at a tissue level, which eliminates the investigation of some essential physiological and pathological responses. One example is the mesenchymal transformation of endothelial cells in response to shear stress. Endothelial to mesenchymal transformation (EndMT) is a valve morphogenic mechanism associated with aortic valve disease initiation. The aortic valve experiences oscillatory shear on the disease‐susceptible fibrosa, and the role of hemodynamics on adult EndMT is unknown. The goal of this work was to develop and characterize a microfluidic bioreactor that applies physiologically relevant laminar or oscillatory shear stresses to endothelial cells and permits the quantitative analysis of 3D cell–extracellular matrix (ECM) interactions. In this study, porcine aortic valve endothelial cells were seeded onto 3D collagen I gels and exposed to different magnitudes of steady or oscillatory shear stress for 48 h. Cells elongated and aligned perpendicular to laminar, but not oscillatory shear. Low steady shear stress (2 dyne/cm2) and oscillatory shear stress upregulated EndMT (ACTA2, Snail, TGFB1) and inflammation (ICAM1, NFKB1) related gene expression, EndMT‐related (αSMA) protein expression, and matrix invasion when compared with static controls or cells exposed to high steady shear (10 and 20 dyne/cm2). Our system enables direct testing of the role of shear stress on endothelial cell mesenchymal transformation in a dynamic, 3D environment and shows that hemodynamics regulate EndMT in adult valve endothelial cells. Biotechnol. Bioeng. 2014;111: 2326–2337. © 2014 Wiley Periodicals, Inc.